Organic Food Consumption Preferences and Perceptions of Food Engineering Students - Ebru AKGÜL; Sultan BARIN; Gülden BAŞYİĞİT KILIÇ; Damla BİLECEN ŞEN (Mehmet Akif Ersoy Üniversitesi Fen Bilimleri Enstitüsü, 2020)
The main objective of this study was to determine the consumption preferences and perceptions to organic food products by consumers. This study was conducted during the 2019-2020 semester with senior Food Engineering students who are studying 12 different universities in Turkey. The 20 statements were asked to be answered by the respondents in accordance with the three-point Likert Scales. With the present study, it was determined that the majority of the respondents in the survey found organic food products healthier, nutritious and reliable. In addition, it was emphasized that organic food products had positive effects on both human health and ecological balance. However, it was determined that the press and media organizations on organic food products did not inform the public sufficiently. Also, it was emphasized that organic food products will be preferred more if their prices were appropriate. In conclusion, it was determined that the respondents wanted to consume organic food products, but they were not preferred due to the high prices of the products and the insufficient reliability from production to consumption. For this reason, the demand for organic food products should be increased primarily by increasing product reliability on consumers, improving prices and providing adequate information.